Composition of fatty oils of the seeds of A. adscendens Roxb., G. sylvestre B.Br. and D. gangeticum (Linn.) DC. - Manivel, P; Dhanani, Tushar; Rana, Virendra; Kumar, Satyanshu (Open Access Journal of Medicinal and Aromatic Plants, 2018)
Asparagus adscendens Roxb. (Family: Asparagaceae), Gymnema sylvestre B.Br. (Family: Asclepiadaceae) and Desmodium gangeticum (Linn.) DC (Fabaceae) are known to possess potent therapeutic properties and are being used in Indian system medicine for curing of many diseases. Different parts of these plant species are reported to have various groups of compound such as phenolics, alkaloids, terpenoids and their glycosides but seeds of these species have not been yet analysed for their fatty oil contents and fatty acids. Thus, the fatty oils from the seeds of A. adscendens, G. sylvestre and D. gangeticum were obtained and analysed for their fatty oil yields. The fatty acid compositions of the seed oil were determined by Gas Chromatography-Mass Spectrophotometry using fatty acid methyl esters. The yields of the crude fatty oils obtained from the crushed seeds by solvent extraction method were found to be 5.92%, 7.79% and 4.39% (on a dry weight basis) for Asparagus adscendens, Gymnema sylvestre and Desmodium gangeticum, respectively. The fatty acid methyl esters of the oils were prepared using an acidic methanol solution followed by separation and purification to obtained pure mixtures of methyl esters of each oil. A total of ten fatty acids (Myristic acid, Palmitoleic acid, Palmitic acid, Linoleic acid, Oleic acid, Elaidic acid, Stearic acid, 11-Eicosanoic acid, Eicosanoic acid, and Behenic acid) were identified in the oils and the common acids were palmitic acid (9.9-15.1%), linoleic acid (19.4-58.5%), oleic acid (22.0-38.7%) and stearic acid (4.5.10.4%). Palmitoleic acid and elaidic acid were absent in the oils of A. adscendens and D. gangeticum but found in the seed oil of G. sylvestre. G. sylvestre and D. gangeticum oils had Behenic acid (0.5% and 8.0%, respectively), however it was absent in A. adscendens seed. This is a first report on the fatty oil composition these plant species.